Pemanfaatan Ekstrak Daun Kelor Sebagai Hand Sanitizer Untuk Meningkatkan Kesejahteraan Disabilitas Pada Forum Komunikasi Disabilitas Kabupaten Kudus (FKDK) - Ulya Ilmilati (Muria Jurnal Layanan Masyarakat, 2021)
FKDK (Kudus Disability Communication Forum) is a special community for people with disabilities located in Kudus Regency. The problem with FKDK is that the skills possessed by FKDK members are still relatively minimal and they have difficulty finding work. Regarding this, we want to provide knowledge, skills and efforts to improve the economy to the Kudus Regency Disability Communication Forum (FKDK) in the domain of empowering its members. Entrepreneurship training in processing Moringa leaves into hand sanitizers is one form of empowering that we will carry out. On the other hand, the use of Moringa leaves in Kudus Regency is currently still limited. In Menawan Village, there are 5 hectares of land planted with Moringa trees as shade plants. Moringa leaf extract has several ingredients including flavonoids, tannins, saponins, alkaloids, and other phenolic compounds that can function as antiseptics, antibacterials, and antioxidants. This content when mixed in a hand sanitizer will not make your skin hot and irritated.